Social impact of happiness on transformational leadership in students from Colombian universities - Zárate-Torres, Rodrigo; Rey-Sarmiento, C. Fabiola; Acosta-Prado, Julio C. (Frontiers in Psychology, 2025)
In the literature, it has been described that affective commitment and transformational leadership are directly related to occupational happiness. In this sense, the present study begins with the premise that subjective happiness may enhance the effectiveness of transformational leadership. For this purpose, the Leadership Practices Inventory (LPI) and the Subjective Happiness Scale (SHS) were applied to a non-probabilistic sample of 215 business administration students in Colombian universities. Bivariate correlation analysis, confirmatory factor analysis, and structural equation modeling were used to examine the relationship between the dimensions of happiness and the five leadership practices. The findings indicate that three happiness items correlate positively with transformational leadership practices, suggesting that happier individuals exhibit more effective leadership behaviors. The proposed theoretical model showed a good fit with the empirical data. In conclusion, promoting happiness in leaders not only improves their performance but also positively impacts organizational productivity.